Study on East Sumba-originated natural pigments for coloring woven fabrics. Issue 1 (September 2020) - Pasaribu, G; Winarni, I
Abstract: East Sumba Regency has long been renowned as the production site for tightly woven items. These woven items afford high economy values, since they are produced with natural-coloring stuffs (renewable-pigments). Pigment-producing plants serve as one of valuable natural sources, which afford beneficial potency for coloring textiles in Indonesia, especially in developing products that sound "back-to-nature". Relevantly, this research aimed to conduct technical assessment and processing of pigment-producing plants associated with natural coloring-agents for fabrics in East Sumba. The methods employed in-depth interviews with various parties, who played essential roles in processing of natural pigments from plant sources; pigment extraction; and chemical tests. Results revealed that utilization of natural pigments still kept going on nowadays by the community in East Sumba to produce tight-woven items. Extraction technique of natural renewable-pigments was still very simple by immersing pigment-producing plants in water. Likewise, so was the technique for coloring threads/yarns with natural pigments by dipping and immersing methods. There were three kinds of plant-derived natural pigments utilized most by the community, with their plant species origins comprising Wora/Nila (Indigofera erecta Thunb), Kambu (Morinda cf.citrifolia L.), and (Symplocos cochinchinensis (Lour.) S. Moore). Further, extraction technique using hot water brought out higher yields of extracted pigments and better fabric-coloring qualities. Activities of tight weaving were commonly used as additional income source. Besides taking considerable time for pigment production process, recipient markets were still not appropriately available. Moreover, currently raw material source for natural pigment became more difficult to obtain. Accordingly, a part of the community began mixing natural pigments with synthetic pigments. In future, pigment-producing plants should expectedly be cultivated more seriously to maintain natural-pigment stocks.